The Tradition of Drinking Jamu and Efforts to Increase the Economic Potential of the Nguter Community, Sukoharjo District - Oktaviani, Diah Ayu; Witasari, Nina; Amalia, Niken Putri (Jurnal Jamu Indonesia, 2025)
The study examined the tradition of Jamu in Nguter District, Sukoharjo Regency, Central Java, which has faced intense competition with modern health products. The community practiced Jamu as part of traditional medicine passed down through generations; however, the tradition has encountered significant challenges in maintaining its existence. The study aimed to identify the obstacles faced by traditional Jamu entrepreneurs and evaluate the efforts made to address these issues. Researchers collected data using historiographic methods, including literature review, field observations, and interviews with Jamu entrepreneurs and consumers. The results of the study showed that Jamu entrepreneurs faced limitations in raw material, inconsistency in quality, and strict licensing regulations. Additionally, Jamu entrepreneurs struggled to compete with modern health product, which were more practical and popular. The conclusion of the study stated that the collaboration between Jamu entrepreneurs and the local government had successfully raised public awareness about the importance of preserving Jamu traditions. The jamu tradition has great potential to support the green economy by relying on sustainable and environmentally friendly natural ingredients. Innovation in packaging and distribution is expected to improve the local economy while preserving the environment. The novelty of the research lies in the integration of cultural, green economic, and health aspects into strategies for preserving the Jamu tradition amid modernization.